An unusual occurrence of Taphrina deformans on apricot trees in Hungary - Kövics, György J. (Acta Agraria Debreceniensis, 2011)
In 2011 a very rare occurence of leaf curl (leaf blaster) disease symptoms of apricot (pathogen: Taphrina deformans) was observed in different apricot plantations in Eastern-Hungary (Debrecen-Józsa, Hajdú-Bihar county) and Northern-Hungary (Bekecs district, Borsod-Abaúj-Zemplén county). The pathogen is common on peach and nectarine resulting serious symptomps and considerable damages in almost every year, although in this year infections of peaches were very low close to the locations. Although there are some references that apricot and even almond are hosts of the fungus but in Hungarian circumstances the infestation on apricot counts unique and rare. Observations were made on symptoms, microscopic photos and measures were taken on exoasci, ascospores and blastospores, respectively. As far as we know this is the first description of Taphrina deformans fungus on apricot in Hungary.